Integrating Artificial Intelligence in IoT Systems: A Systematic Review of Recent Advances and Application - Shir Ahmad Hamidi; Fareed Ullah Hashimi; Ajmal Rahmati (Journal of Computer Science Advancements, 2024)
This study explores the intersection of Artificial Intelligence (AI) and the Internet of Things (IoT), focusing on contemporary trends, challenges, and emerging applications. The key objectives are assessing the improvements in efficiency, scalability, and automation as a result of AIoT integration, identifying significant challenges realized during implementation, and checking the potential future application in various sectors. A literature review about all aspects was conducted on MDPI, ScienceDirect, IEEE Xplore, and Springer for documents spanning from 2019 to 2024. The review brought to light the significant progress in AIoT: real-time data processing, predictive maintenance, and smart home automation. Core challenges include data security, interoperability, and algorithm manipulation. Future applications using AI on IoT are expected to revolutionize paradigms such as healthcare, smart cities, and agriculture, providing better efficiency and innovation. Newly emerging paradigms from AIoT bear the potential for transformation, emphasizing that related challenges must be adequately tackled for them to result in implementation.